Memberdayakan Siswa Sebagai Pembelajar Aktif Dengan Menggunakan Peran Pembelajaran Tematik Dalam Pengembangan Kemandirian Belajar Siswa Sekolah Dasar - Aisyah, Nurul; Dedia, Selsa; Sofiyah, Khotna (PT. Alahyan Publisher Sukabumi, 2024)
Thematic learning is a learning approach that integrates various lesson content into one particular theme. This approach provides students with the opportunity to learn concepts in a holistic and integrated manner. One of the main benefits of thematic learning is that it encourages independent learning in students. Through exploring themes that span various disciplines, students are trained to take initiative in learning, build connections between concepts, and develop critical thinking skills. This journal examines the role of thematic learning in empowering students as active and independent learners. The discussion includes strategies that teachers can implement to facilitate student learning independence, such as project-based learning, using a variety of learning resources, and providing opportunities for collaborative learning.